Cortezas de árboles y arbustos del Parque Nacional Palo Verde - Vargas Rojas, Gustavo (Editorial Universidad Nacional (EUNA), 2018)
For lovers of trees and shrubs, Editorial UNA presents four volumes of the digital field guide: Barks of Trees and Shrubs of the Palo Verde National Park. Anyone who walks through the forests of Costa Rica will find fascinating the diversity of trees that provide shade and food for the rest of the organisms. This diversity is reflected in the shape, texture and color of the different barks. The digital guides of the bark of trees and shrubs of the Palo Verde National Park are then a very practical tool to identify the different species of trees in the Park; since in many cases it is very difficult to obtain the leaves, flowers and fruits to carry out this task. In a place like the Palo Verde National Park and in a time like the dry season, the forest trees lose their leaves in response to avoid water loss (they avoid losing water through perspiration through their leaves). At this time the trees will not have leaves, flowers or fruits to be identified, only the bark gives us the possibility of knowing their scientific and vernacular name. The purpose of the digital guides (barks of trees and shrubs of the Palo Verde National Park) is to provide the walker interested in trees with a practical tool to identify their names, which would initiate an unsuspected explosion of scientific and cultural knowledge.